2010
DOI: 10.1149/1.3251285
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Atomic Layer Deposition of Ruthenium from N,N-Dimethyl-1-ruthenocenylethylamine

Abstract: Ruthenium thin films were grown by atomic layer deposition from N,N -dimethyl-1-ruthenocenylethylamine precursor. The growth was examined in the substrate temperature range of 325–500°C . The growth rate increased with the substrate temperature but was quite stable between 400 and 450°C . The films typically consisted of polycrystalline hexagonal ruthenium metal with a resistivity in the range of 10–20μΩcm when the film thickness was 10 nm and above. A resistivity of 49μΩcm could be achieved in the film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 29 publications
4
29
0
Order By: Relevance
“…This is about twice as high as the growth obtained with other metalorganic precursors, such as Ru͑EtCp͒ 2 , DER, or EMR. 21,24,31 The growth-per-cycle is, however, quite similar to one of the new Ru ALD processes recently reported by Eom et al 30 Using the open-ring compound C 16 H 22 Ru, a similarly high growth-per-cycle of 0.9 Å was obtained at 220°C.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…This is about twice as high as the growth obtained with other metalorganic precursors, such as Ru͑EtCp͒ 2 , DER, or EMR. 21,24,31 The growth-per-cycle is, however, quite similar to one of the new Ru ALD processes recently reported by Eom et al 30 Using the open-ring compound C 16 H 22 Ru, a similarly high growth-per-cycle of 0.9 Å was obtained at 220°C.…”
Section: Resultssupporting
confidence: 79%
“…However, based on the results reported, the high surface roughness can mainly be attributed to the combination of a relatively high substrate temperature and use of O 2 ͑plasma͒ as co-reactant. 12 roughness values ͑1.7 nm for a 5 nm thin film͒ for Ru prepared from EMR and O 2 at high substrate temperatures ͑T ϳ 400°C͒, 31 and Park et al 33 reported a surface roughness of 1.4 nm for a film of only ϳ3.1 nm thickness prepared from CpRu͑CO͒ 2 Et and O 2 at 300°C. Using a ruthenium amidanate precursor and O 2 , Wang et al 32 found that the surface roughness and grain size increase with longer O 2 gas exposures ͑with a maximum roughness of ϳ2.5 nm for an ϳ30 nm thick film͒ with the grain size distribution becoming also non-uniform.…”
Section: 2431mentioning
confidence: 98%
See 2 more Smart Citations
“…To mention a few, (2,4-dimethylpentadienyl) (ethylcyclopentadienyl)ruthenium [24], bis (2,4-dimethylpentadienyl) ruthenium [25], triruthenium dodecacarbonyl [9] and bis(2,2,6, 6-tetramethyl-heptane-3,5-dionato)(1,5-cyclooctadiene)ruthenium [26], have been applied as Ru precursors in CVD process. Bis(cyclopentadienyl)ruthenium [18][19][20], bis(ethylcyclopentadienyl)ruthenium [19,27], N,N-dimethyl-1-ruthenocene [28], 2,4-(dimethylpentadienyl) (ethylcyclopentadienyl) ruthenium, i.e. DER [29], (methylcyclopentadienyl)(pyrrolyl)ruthenium [15] or isopropylmethylbenzene-cyclohexadiene-ruthenium [2] have been adapted to ALD processes.…”
Section: Introductionmentioning
confidence: 99%